Knowledge, Supervision, and Availability of Facilities and the Use of Personal Protective Equipment among Welding Workers in the Shipyard Industry - Trisna Dewita; Ice Irawati (Sarana Ilmu Indonesia (Salnesia), 2026)
Welding workers face serious occupational hazards including exposure to metal fumes, ultraviolet radiation, sparks, and musculoskeletal disorders. According to the International Labour Organization (ILO, 2023), nearly 3 million deaths occur annually due to occupational accidents and diseases. In Batam, from January to September 2025, 4,610 cases of occupational accidents were recorded, reflecting an OHS emergency. This study aimed to empirically analyze factors statistically related to the use of PPE among welding workers at a large shipyard company in Batam City. A cross-sectional quantitative design was used and implemented from March to August 2025. A total of 95 welders from main contractor and subcontractor units were recruited using purposive sampling based on predetermined inclusion criteria. Bivariate analysis using the Chi-square test (α = 0.05) was conducted to examine the relationship between independent variables (knowledge, supervision, and availability of PPE) and the fulfillment of PPE use. The results showed a statistically significant relationship between OHS knowledge and PPE use (p <0.001), supervision and PPE use (p <0.001), and facility availability and PPE use (p <0.001). This confirmed that improved OHS technology, adequate facilities, and consistent supervision play a significant role in improving worker compliance with PPE use.